Identification of the Barriers to Business in Slovakia - Strenitzerova, Mariana; Garbarova, Miriam (Communications - Scientific letters of the University of Zilina, 2017)
Barriers are the problems with which every company meets. These problems affect companies negatively. The aim of this paper is to identify major barriers in selected industry of the Slovak business environment. To fulfill the aim of the paper, a primary research, based on the methods of querying, analysis, comparison and selection, was conducted. The questionnaire was focused on identifying barriers in the Slovak business environment from the view of advertising agencies operating in the Zilina region. We can conclude that respondents can be divided into three groups: companies whose business is affected by the barriers, companies whose business is partly influenced by barriers, companies whose business is not affected by the barriers. We can deduce, according to respondents, that the main barrier to business is represented by the work of public administrative bodies.